Housing Correlates in Pregnant and Parenting Women Using Methamphetamine and Accessing Psychiatric Care - Petzold, Johannes; Rehmet, Laura; Weber, Benjamin; Spreer, Maik; Krüger, Maria; Zimmermann, Ulrich S.; Pilhatsch, Maximilian (Frontiers in Psychiatry, 2022)
Background: Integrated care is a promising model for pregnant and parenting women with problems related to methamphetamine use. Yet more research is imperative to guide services for this vulnerable population as methamphetamine use contributes to housing instability, which is associated with heavier use and overdose death. Method: This prospective observational study analyzed how housing at discharge from psychiatric care was related to patient characteristics, program participation, and aftercare in 102 pregnant and/or parenting women. Results: Twelve of 23 women who were unstably housed at admission (3 of 6 homeless) achieved stable housing by discharge from integrated care. Women were more likely unstably housed at discharge when unstably housed at admission, single, living apart from at least one minor, or when the other parent had a substance use disorder (p-values < 0.05). Unstably housed women at discharge were also more likely to have used social and inpatient services, and to transition to inpatient rehabilitation (p-values < 0.05). Among baseline characteristics, logistic regression identified unstable housing at admission (OR = 6.07) and being single (OR = 4.01) as the strongest unique contributors to unstable housing at discharge (p-values < 0.05). Conclusion: Unstably housed women and single women seem particularly at risk of remaining in precarious living conditions despite accessing integrated care for problems associated with methamphetamine use. Future work should investigate whether stronger partnerships with government and community agencies could be a way forward to help these women attain and maintain stable housing.